2019
DOI: 10.1080/17461391.2019.1575913
|View full text |Cite
|
Sign up to set email alerts
|

Does maturation influence neuromuscular performance and muscle damage after competitive match‐play in youth male soccer players?

Abstract: Poor neuromuscular control and fatigue have been proposed as a risk factor for noncontact injuries especially around peak height velocity (PHV). This study explored the effects of competitive soccer match-play on neuromuscular performance and muscle damage in male youth soccer players. Methods: 24 youth players aged 13-16y were split into a PHV group (-0.5 to 0.5y) and post PHV group (1.0-2.5y) based on maturity offset. Leg stiffness, reactive strength index (RSI), muscle activation, creatine kinase (CK), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…One explanation could be that early-maturing players are more physiologically advanced in the maturity process and capable of performing more intensive work, resulting in higher muscle damage 2 and consequent (perceived) delayed-onset muscle soreness (DOMS). 16,27 Mature players may have attained a certain level of sport-specific muscle adaptation, reducing the incidence of DOMS. 45 A higher incidence of ligament sprain, strain, and adductor injuries was observed in mature players.…”
Section: Skeletal Maturity and Other Types Of Injurymentioning
confidence: 99%
“…One explanation could be that early-maturing players are more physiologically advanced in the maturity process and capable of performing more intensive work, resulting in higher muscle damage 2 and consequent (perceived) delayed-onset muscle soreness (DOMS). 16,27 Mature players may have attained a certain level of sport-specific muscle adaptation, reducing the incidence of DOMS. 45 A higher incidence of ligament sprain, strain, and adductor injuries was observed in mature players.…”
Section: Skeletal Maturity and Other Types Of Injurymentioning
confidence: 99%
“…14,[25][26][27] In the applied setting, this categorisation may be utilised to implement maturity specific interventions, produce reports or inform talent (de)selection decisions. 4 Several studies have used such classifications to assess the impact of maturation on performance, such as speed, 25 neuromuscular performance 28 and aerobic endurance. 29 Due to error, typical bandwidth thresholds of AE1-year, or AE0.5-years have been utilised to determine whether individuals are pre-, circa-or post-PHV.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the current level of fatigue was not monitored in players. In this context, interesting results are presented in the already mentioned study on youth soccer players aged 13-16 y by De Ste Croix et al [43]. The authors reported that the influence of competitive match-play on neuromuscular function evaluated by muscle activity recorded using surface polyelectromyography and RSI was found to be similar in male youth around the time of peak height velocity and those post peak height velocity.…”
Section: Changes In Emgmentioning
confidence: 89%
“…In the BF there was a trend of a reduction; however, this was nonsignificant. Surprisingly, in the most recent study by De Ste Croix et al [43], which explored the effects of competitive soccer match-play on neuromuscular performance and muscle damage in 13-16y players (further split into PHV group and post PHV group based on maturity off-set), no significant changes in muscle activation of H and Q muscles were observed. Considering all the above-mentioned studies in which elite youth soccer players were observed, the differences in changes of muscle activity could be, in our opinion, explained by differences in the applied fatigue exercise (soccer-specific fatigue protocol and competitive match-play, respectively).…”
Section: Changes In Emgmentioning
confidence: 92%
See 1 more Smart Citation